Penerapan Model Pembelajaran Inkuiri Terbimbing Berbentuk Augmented Reality pada Peserta Didik untuk Meningkatkan Minat dan Pemahaman Konsep IPA - Aryani, Pramita Rosma; Akhlis, Isa; Subali, Bambang (UPEJ Unnes Physics Education Journal, 2019)
This research aims at determining the influence of guided inquiry learning model supported by media Augmented Reality to increase the interest and understanding of science concepts. This research applied experimental design with Pretest-Posttest Group type. Samples were taken using simple random sampling in 8 Magelang Senior High School year 2016/2017 with VII G which received treatment using guided inquiry learning model supported by media Augmented Reality as experimental class and VII H which received using guided inquiry learning model without media Augmented Reality treatment as control class. The indicator used to measure learning interest is an feel happy in lerning, attention, attachment in learning, participating in learning, satisfaction, and interesting in learning. ?Students interest test after learning using guided inquiry learning model supported by media Augmented Reality shows an increased interest in learning in every aspect. The result showed that the average score of pretest was (37,35) and the average score of postest was (93,38). The relationship between interest and understanding of concepts is indicated by the correlation rate of 0.89 with the influence rate of 64%.  Improved understanding of concepts was shown ny the N-gain test (0,89) with ?high criterion?.  In conclution, guided inquiry learning model supported by media Augmented Reality can to improve increase the interest and students?understanding of science concepts.